Effect of L-carnitine Supplementation on Health Indicators of Untrained Men Over a Period of Resistance Training: A Randomized, Placebo-Controlled Trial - Samadi Mohammad; Hamid Agha Alinejad; Mahvash Jafari; Kazem Khalagi; Foad Asjodi; Ebrahim Falah (Iranian Association of Health Education and Health Promotion, 2014)
Background and objective: Oxidative stress is a consequence of professional sports that could endanger the health of athletes. This study aimed to determine the effect of L-carnitine supplementation on health indicators of untrained men over a period of resistance training. Methods: A double-blinded, randomized controlled trial study conducted on twenty-four healthy untrained male. Study subjects were randomly assigned to two equal groups, L-carnitine and placebo (n=12). Both groups participated in 8 weeks resistance training period and supplementation of 2 g/day L-carnitine or placebo (maltodextrin) was done. Anthropometric measurements, dietary intakes and blood biochemical parameters including glutathione, malondialdehyde, superoxide dismutase and catalase were measured at the beginning and end of the study. Results: At the end of the study in L-carnitine group, mean serum glutathione (GSH) were significantly increased (p<0.05) and mean serum malondialdehyde (MDA) were significantly decreased (p<0.05). Also mean of these parameters between the two groups were significantly different from each other (p <0.5). Enzyme activity of superoxide dismutase (SOD) and catalase (CAT) were significantly increased in both groups but the increase was higher in the supplement group (p <0.01). Conclusion: In this study, supplementation with 2 grams of L-carnitine per day for 8 weeks, increased serum glutathione,superoxide dismutase and catalase enzyme activity and decreased serum malondialdehyde significantly. Paper Type: Research paper